Association between Minimum Dietary Diversity and Nutritional Status among Children Aged 6 to 24 Months in Terengganu - Zulkifli, Nur Arifah; Wee, Bee Suan (Jurnal Gizi dan Pangan, 2025)
This cross-sectional study aimed to determine the association between food consumption quality, as determined by Minimum Dietary Diversity (MDD), and children’s nutritional status using anthropometric measurements. A total of 287 children (150 boys, 147 girls) aged 6 to 24 months from Kuala Nerus and Kuala Terengganu participated in this study through purposive sampling. Socio-demographics and food consumption of children were collected through interviews with the mother. Anthropometric comprised weight, height, while nutritional status was determined based on WHO Child Growth Standards. MDD was assessed using WHO Infant and Young Child Feeding (IYCF) Indicators Questionnaire. Children achieving the MDD were rated on four or more dietary variety scores, while those receiving less than four were categorized as "not achieving" the MDD. Most of the children (98.6%) were Malay, with 69.3% aged between 12 to 24 months and 30.7% aged between 6 to 11 months. The prevalence of stunting, wasting, and underweight was 25.8%. 6.6% and 14.6%, respectively. The proportion of children achieving MDD was 90.2%. No significant association existed between MDD and stunting, wasting, or being underweight. However, Pearson’s Chi-Square test affirms that consumption of dairy products was significantly associated with stunting among children (p=0.001). In conclusion, dairy products significantly prevent stunting in children, and their continuation should be emphasized for the first two years of life after exclusive breastfeeding in health promotion programs.